International Symposium onInformation Theory, 2004. ISIT 2004. Proceedings.
DOI: 10.1109/isit.2004.1365456
|View full text |Cite
|
Sign up to set email alerts
|

Performance enhancements for algebraic soft decision decoding of reed-solomon codes

Abstract: -In an attempt to determine the ultimate capabilities of the Sudan/Guruswami-Sudan/Kötter-Vardy algebraic soft decision decoding algorithm for Reed-Solomon codes, we present a new method, based on the Chernoff bound, for constructing multiplicity matrices. In many cases, this technique predicts that the potential performance of ASD decoding of RS codes is significantly better than previously thought.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 6 publications
0
16
0
Order By: Relevance
“…Other algorithms of [10] and [11] minimize the error probability directly. The algorithm of [10] (Gauss) assumes a Gaussian distribution of the score, while that of [11] (Chernoff) minimizes a Chernoff bound on the error probability. The later appears to have the best performance.…”
Section: Algebraic Soft Decodingmentioning
confidence: 99%
See 2 more Smart Citations
“…Other algorithms of [10] and [11] minimize the error probability directly. The algorithm of [10] (Gauss) assumes a Gaussian distribution of the score, while that of [11] (Chernoff) minimizes a Chernoff bound on the error probability. The later appears to have the best performance.…”
Section: Algebraic Soft Decodingmentioning
confidence: 99%
“…Previous multiplicity assignment algorithms [9]- [11] assumed approximate a posteriori probabilities. The problem is simplified by assuming that the transmitted codeword is drawn uniformly from .…”
Section: Hybrid Abp-asd List Decoding Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, previous soft-decision decoding algorithms either can only achieve limited coding gain or have very high complexity. Algebraic soft-decision (ASD) decoding algorithms [2], [3], [4], [5], [6], [7] for RS codes have been developed recently. By incorporating the probability information from the channel into the algebraic interpolation process developed by Sudan and Guruswami [8], [9], these algorithms can achieve significant coding gain with a complexity that is polynomial with respect to the codeword length.…”
Section: Introductionmentioning
confidence: 99%
“…They also showed that for codes of infinite length the best way to choose the value of m is by making it proportional to the soft information available for each point. In [6], [7] and [8] there were presented some multiplicity assignment strategies which were optimized for infinite-length codes through complex numeric algorithms. However for codes of finite length, an optimum multiplicity assignment strategy is still an open problem.…”
Section: Introductionmentioning
confidence: 99%